2015
DOI: 10.1186/s13065-015-0102-7
|View full text |Cite
|
Sign up to set email alerts
|

A facile, stereoselective, one-pot synthesis of resveratrol derivatives

Abstract: BackgroundCompounds based on trans-1,2-diphenylethene are the subject of intense interest both for their optical properties and as potential leads for drug discovery, as a consequence of their anticancer, anti-inflammatory and antioxidant properties. Perhaps the best known of these is trans-3,5,4′-trihydroxystilbene (resveratrol), that has been identified as a promising lead in the search for anti-ageing therapeutics.ResultsWe report here a new, convenient, one-pot stereo-selective synthesis of resveratrol and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…1a ) with the goal of identifying compounds that could restore splicing factor expression to levels comparable with those seen in young cells, but with differing effects on SIRT1 activation and the senescence-associated secretory phenotype (SASP) to allow assessment of molecular mechanism. Synthesis of the backbone was achieved as previously reported [ 26 ], with additional functionality and diversity achieved via functional group interconversion (Fig. 1b ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1a ) with the goal of identifying compounds that could restore splicing factor expression to levels comparable with those seen in young cells, but with differing effects on SIRT1 activation and the senescence-associated secretory phenotype (SASP) to allow assessment of molecular mechanism. Synthesis of the backbone was achieved as previously reported [ 26 ], with additional functionality and diversity achieved via functional group interconversion (Fig. 1b ).…”
Section: Resultsmentioning
confidence: 99%
“…Resveratrol (Sigma Aldrich, UK; 1 ) was used to synthesise dihydroresveratrol 2 as reported previously [ 47 ]. ( E )-N-(4-(3,5-Dimethoxystyryl)phenyl) methanesulfonamide 3 was synthesised from the previously reported nitro-substituted analogue 7 via an Fe/NH 4 Cl reduction to give amine 8 [ 26 ], followed by sulfonylation with methanesulfonyl chloride (Fig. 1b ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Resveratrol (trans-3,5,4'-trihydroxystilbene) is an excellent candidate for a molecule which modulates multiple hallmark mechanisms simultaneously. Although initially proposed to act as a dietary restriction mimetic based in part on the observation that resveratrol supplementation of the standard diet of laboratory mice induces shifts in gene expression similar to those seen when animals undergo calorie restriction (Barger et al 2008, Bhullar and Hubbard;2015). A wealth of data have subsequently become available consistent with resveratrol affecting proteostasis (Corpas et al 2019), stem cell exhaustion (Safaeinejad et al 2018), mitochondrial dysfunction (de Oliveira et al 216), genomic instability (Stopper et al 2005) and intercellular communication (Huang et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Several synthetic approaches have been described for the synthesis of resveratrol, carried out by Wittig [ 149 ] or Horner-Wadsworth-Emmons reactions [ 150 ], Perkin condensations [ 151 ], and also through metal-catalysed processes, such as cross-metathesis [ 152 ] or cross-coupling reactions [ 153 , 154 ]. The most recent synthesis of resveratrol has been carried out by El-Deeb et al [ 155 ] and is shown in Scheme 29 .…”
Section: Synthesis and Mode Of Action Of Glyco-based And Aromatic mentioning
confidence: 99%